Effect of microstructure on electrical properties of thin film alumina capacitor with metal electrode - Jeong, M.-S.; Ju, B.-K.; Oh, Y.-J.; Lee, J.-K. (2011)
The power capacitors used as vehicle inverters must have a small size, high capacitance, high voltage, fast response and wide operating temperature. Our thin film capacitor was fabricated by alumina layers as a dielectric material and a metal electrode instead of a liquid electrolyte in an aluminum electrolytic capacitor. We analyzed the micro structures and the electrical properties of the thin film capacitors fabricated by nano-channel alumina and metal electrodes. The metal electrode was filled into the alumina nano-channel by electroless nickel plating with polyethylene glycol and a palladium catalyst. The spherical metals were formed inside the alumina nano pores. The breakdown voltage and leakage current increased by the chemical reaction of the alumina layer and PdCl2 solution. The thickness of the electroless plated nickel layer was 300 nm. We observed the nano pores in the interface between the alumina layer and the metal electrode. The alumina capacitors with nickel electrodes had a capacitance density of 100 nF/cm2, dielectric loss of 0.01, breakdown voltage of 0.7MV/cm and leakage current of 104 μA.
Keywords: Alumina films; Alumina layers; Aluminum electrolytic capacitors; Capacitance density; Electroless; Electroless Ni plating; Electroless nickel plating; Fast response; High voltage; Liquid electrolytes; Metal electrodes; Nano channels; Nickel electrode; Nickel layers; Operating temperature; Palladium catalyst; Power capacitor; Small size; Thin film alumina; Thin-film capacitors; Capacitance; Catalysts; Dielectric losses; Dielectric materials; Electric breakdown; Electrodes; Glycols; Metals; Nickel; Nickel plating; Palladium; Polyethylene glycols; Polyethylenes; Thermoplastics; Thin film circuits; Thin films; Electrolytic capacitors